The time spent sitting does not always mean a low level of physical activity - Ewelina Matusiak-Wieczorek; Anna Lipert; Ewa Kochan; Anna Jegier (BMC, 2020)
Abstract Background The problem of spending most of the day in a sitting position concerns all people, regardless of their age. Unfortunately, this trend is more and more often observed among young people. The aim of the study was to assess self-reported physical activity and time spent sitting among students of different fields of health related faculty. Methods The study group included 216 students (22.3 ± 1.8 years of age) of the Medical University of Lodz: physiotherapy students (n = 101), pharmacy students (n = 73), and dietetics students (n = 42). The time spent sitting and physical activity level were assessed based on the International Physical Activity Questionnaire-long version. Results The time spent sitting among health related faculty students was on average more than 46 h a week (2781.8 ± 1238.5 MET-minutes/week). Regarding all the students the pharmacy students spent most time sitting (3086.0 ± 1032.1 MET-minutes/week), while the dietetics students spent the least (2215.7 ± 1230.1 MET-minutes/week). Taking into account the physical activity level almost 65% of all the students were in a high category (mainly physiotherapy students). Only 1.4% of all the surveyed students were classified as the low physical activity category. Statistical analysis showed no significant differences (P = 0.6880) between the time spent sitting and level of physical activity among all students. Conclusions Students of medical universities spend too much hours on sitting, mostly 5-8 h a day. Despite this, they undertake various activities due to which their level of physical activity is moderate or even high. Therefore, it cannot be unequivocally stated that there is a relationship between the time spent sitting and physical activity level.